Clinical and genetic features in autosomal recessive and X-linked Alport syndrome - Wang, Yanyan; Sivakumar, Vanessa; Mohammad, Mardhiah; Colville, Deb; Storey, Helen; Flinter, Frances; Dagher, Hayat; Savige, Judy (Springer Berlin Heidelberg, 2014)
Background This study determined the family history and clinical features that suggested autosomal recessive rather than X-linked Alport syndrome.